'We were not even trained to have an opinion': Political socialization of Arabs in Israel. Issue 2 (1st June 2022) - Hisherik, Michal; Gindi, Shahar
There are two main paradigms regarding political socialization. The early-years-of-life hypothesis emphasizes the importance of political socialization in the early years, while the life-long hypothesis argues that political socialization is shaped continuously throughout life. The literature on the topic concentrates on seminal events and their impact on political socialization. In this study, we examined these hypotheses in the unique context of Arab teachers in Jewish schools in Israel. The teachers spoke about the culture of silence about politics that characterized their childhood and their inhibitions regarding engaging in politics. Entering work in a predominantly Jewish environment highlighted the social mechanisms and minority‐majority power relations that preserve Arab citizens' political oppression. The teachers all indicated a process by which they become more politically aware, while their willingness to be politically active varies. The political dialogue between the Jewish and Arab teachers begins hesitantly but increases with time. The findings demonstrate political socialization as a life-long process that is shaped by everyday contact with the majority group and not only by historical/seminal events. It is demonstrated that schools cannot be sterilized from political influences, and the potential of Arab teachers in Jewish schools in defusing the polarization in Israeli society is emphasized.